A lipidomic approach to identify cold-induced changes in Arabidopsis membrane lipid composition - Vu, Hieu Sy; Shiva, Sunitha; Hall, Aaron Smalter; Welti, Ruth (Springer Science+Business Media, 2014)
Lipidomic analysis using electrospray ionization triple quadrupole mass spectrometry can be employed to monitor lipid changes that occur during cold and freezing stress of plants. Here we describe the analysis of Arabidopsis thaliana polar glycerolipids with normal and oxidized acyl chains, sampled during cold and freezing treatments. Mass spectral data are processed using the online capabilities of LipidomeDB Data Calculation Environment.
Keywords: Cold acclimation; Freezing; Post-freezing recovery; Lipidomics; Galactolipid; Phospholipid; Oxidized lipid; Triple quadrupole; Mass spectrometry